The importance of technical visits in study trips for technical courses integrated with high school: Case of the Chemistry Technician class at IFMA – São Luís Monte Castelo campus (Research, Society and Development, 2024)
In Brazil, Integrated Vocational and Technical Education at the Secondary Level (EPTN) requires that technical and secondary education content be planned and delivered in an integrated manner, promoting the comprehensive education of students. Teachers should not limit themselves to classroom activities, as students need to engage with and experience the transformations in the environment in which they live. Technical visits play a crucial role in this teaching and learning process. This study aims to analyze the importance of a study trip to the Industrial Park of Fortaleza-CE for the professional and civic education of students in the technical Chemistry course. A descriptive and analytical methodology was used, combining both quantitative and qualitative data collected through questionnaires. For 48.4% of the students, this was their first interstate trip. All participants (100%) considered the trip “important” or “very important” for their education, both in terms of general knowledge and technical expertise. Additionally, 93.6% regarded the trip as “important” or “very important” for their personal and civic development. Every student (100%) agreed that the trip was “important” or “very important” for integrating the knowledge learned in class. Furthermore, 100% of the class would recommend study trips to all EPTNM students. These activities expand students’ worldviews, cultures, citizenship, respect, and responsibility, as well as enhancing their knowledge, teamwork, and preparation for the workforce. It is recommended that teaching plans include study visits and trips, with efforts from administrators to ensure their availability for all classes.